Вы находитесь на странице: 1из 4

Please solve the following problems:

( 7−6 .35 ) ÷ 6 . 5+9 . 9


1. Find the value of 5 169
(1 .2 ÷ 36+1 .2 ÷ 0 .25−1 )÷
16 24

Solving:

7−6.35
+ 9.9
6.5
1,2 1,2 5
( + −1 )
36 0,25 16
169
24

Subtracting 7-6.35=0,65

7−6.35 0,65
+ 9.9 + 9.9
6.5 6.5
=
1,2 1,2 5 1,2 1,2 5
( + −1 ) ( + −1 )
36 0,25 16 36 0,25 16
169 169
24 24

a a∗c
=
Applying fraction properties b b
c

1,2 1,2 5 1,2 1,2 5


( + −1 ) 24 ( + − )
36 0,25 16 36 0,25 16
=
169 169
24

1,2 1,2 5
Solving ( + −1 )
36 0,25 16

1,2 1,2 5
24( + − )
36 0,25 16 24∗4,52083 …
=
169 169

Replacing in the original equation


0 . 65 0.6 5
+ 9.9 +9.9
6.5 6.5
=
1,2 1,2 5 24∗4,52083 …
( + −1 )
36 0,25 16 169
169
24

a a∗c
=
Applying fraction properties b b
c

0.65 0.65
+9.9 169∗( + 9.9)
6.5 6.5
=
24∗4,52083 … 24∗4,52083 …
169
Solving 24∗4,52083 …

0.65 0.65
169∗( +9.9) 169∗( +9.9)
6.5 6.5
=
24∗4,52083… 108,5

169 0.65
Dividing and solving ( + 9.9)
108,5 6.5

0.65
169∗( +9.9)
6.5
=1,55760 …∗( 0,1+9.9 )=1,55760 …
108,5

2. Solve for x
x +1 x2 −1
2
− =23
x−4 x +3

To find minimum common multiple of x−4 , x+3 :( x−4 )( x+3)


Multiplying for minimum common multiple ( x−4)( x +3)

x2 +1 x 2−1
(x−4 )(x+3)− (x−4 )( x+3)=23(x−4)(x+ 3)
x−4 x+3

Simplying

( x 2+ 1)(x +3)−( x 2−1)( x−4)=23( x−4 )(x+3)

Expanding ( x 2+ 1)( x +3)−(x 2−1)( x−4)


( x 2 +1 ) ( x +3 ) −( x 2−1 ) ( x−4 )=x 3 +3 x2 + x +3−x 3 + 4 x 2+ x−4=7 x 2+ 2 x−1
Solving 23(x−4)(x +3)

23 ( x−4 ) ( x+3 )=23 x 2−23 x−276


Replacing in the original equation
7 x 2+ 2 x−1=23 x 2−23 x−276
7 x 2+ 2 x +275=23 x 2−23 x
Adding 23 x

7 x 2+ 25 x+ 275=23 x 2
Subtract 23 x 2

−16 x 2+ 25 x +275=0

−b ± √ b2−4 ac , a=−16 , b=25 , c=275


Solving with x 1,2=
2a

−25+ √ −162−4(−16)275 −55


x 1= =
2(−16) 16
2
−25− √−16 −4 (−16) 275
x 1= =5
2(−16)

1 1
3. Find the value of
√ 25 log 6 5
+ 49 log 8 7

1
Solving for log 6 5
25

1
=1,11328 … .
log 6 5
1
Replacing in log 6 5
25

251,11328 … =36

1
Solving for log8 7
49
1
=1,06862 …. .
log 8 7

1
Replacing in log8 7
49
1
log8 7
49 =491,06862 =64
Replacing in the original equation and solving

√ 36+64=√ 100=10

Оценить